DEATH AND AFTERLIFE - V. F. Vineeth (Journal of Dharma, 2012)
Human being is a person walking to his own death. Therefore, he is called martya: mortal, born to die. The Sanskrit word for death is mrtya, is derived from the Sanskrit root mr (means to die). The Latin equivalent is mors (mortis): death. As per the word meaning, every human being is born to die. This is because as an embodied being, the human being is subject to the operative dynamics of time. He is born in time, called to live in time, and destined also to leave the time-zone of his existence. This takes us to the questions on time and the nature temporality. What it means to say that human beings are temporal beings is of fundamental interest for philosophical investigations. Are we born in time only to cease to exist after a few years of existence? Is death really the end of the life-span or is there an afterlife? These are fundamental questions raised by all human beings.